Transnational moments of change : Europe 1945, 1968, 1989 - Horn, Gerd-Rainer 1955- Hrsg; Kenney, Padraic 1963- (Rowman & Littlefield, 2004)
Pt. one: 1945 ; Recasting democracy? Communist parties facing change and reconstruction in post-war Europe / Aldo Agosti ; Window of opportunities, or, Trompe l'oeil? The myth of labor unity in Western Europe after 1945 / Patrick Pasture ; Liberated cones in Northern Italy and Southeastern France: the cases of the Alto Tortonese and the Vercors / Anna Balzarro ; The influence of socialist realism in Italy during the immediate postwar period / Juan José Gómez Gutiérrez -- pt. two: 1968 ; "1968" and "The cultural revolution of the long sixties (c. 1958-c. 1974)" / Arthur Marwick ; The working class dimension of "1968" / Gerd-Rainer Horn ; 1968 East and West: Visions of political change and student protest from across the Iron Curtain / Paulina Bren ; Echoes of provocation: "1968" and the women's movements in France and Germany / Kristina Schulz -- pt. three: 1989 ; The global context of 1989 / Jarle Simensen ; The development of a Green Opposition in Czechoslovakia: the role of international contacts / Miroslav Vanek ; A transcontinental movement of citizens? Strategic debates in the 1980s western peace movement / Patrick Burke ; Opposition networks and transnational diffusion in the revolutions of 1989 / Padraic Kenney.